The Effects of Lycosoid Spider Density within Trophic Cascades - Diana Marie Saintignon; Erica Kistner (The Journal of Undergraduate Research, 2013)
In a trophic cascade an organism can indirectly have a beneficial impact on another organism by directly impacting an intermediate organism. This idea is useful in conservational practices because these organisms, known as keystone predators, can be used to control the populations lower down on the food chain, ultimately benefiting producers. In the grasslands of western Montana, grasshoppers are considered pests by local farmers. In this experiment, we tested whether Lycosoid spiders play the role of a keystone predator within this ecosystem by preying on early developmental stage grasshoppers. This project also looked into how the grasshoppers reacted to the Lycosoid spider presence, and if a potentially resulting trophic cascade had a positive effect on plant biomass. Data was collected at the National Bison Range, MT at an undisturbed grassland in July. Ten early-stage grasshoppers were placed in wire mesh cages with 0, 1, or 2 Lycasoid spiders and observations were recorded over an eleven day period. Results showed that while early developmental stage Melanoplus sanguinipes and Melanoplus femurubrum exhibited risk behaviors in the presence of Lycosoid spiders and that the number of individuals practicing these behaviors increased with the number of spiders added, no tropic cascade resulted.